2019
DOI: 10.5194/acp-19-6551-2019
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of the ability of the Ozone Monitoring Instrument (OMI) to observe boundary layer ozone pollution across China: application to 2005–2017 ozone trends

Abstract: Abstract. Nadir-viewing satellite observations of tropospheric ozone in the UV have been shown to have some sensitivity to boundary layer ozone pollution episodes, but so far they have not yet been compared to surface ozone observations collected by large-scale monitoring networks. Here we use 2013–2017 surface ozone data from China's new Ministry of Ecology and Environment (MEE) network of ∼ 1000 sites, together with vertical profiles from ozonesondes and aircraft, to quantify the ability of tropospheric ozon… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 39 publications
(42 reference statements)
4
59
0
Order By: Relevance
“…Silver et al (2018) found the annual mean MDA8 ozone has increased significantly (p<0.05) at around 50% of the over 1000 stations across China from 2015 to 2017, with a median rate of 4.6 µg m -3 year -1 . The increasing trend over eastern China was also captured by the OMI satellite records of tropospheric ozone, reported by Shen et al (2019). The absolute increasing trend (in a unit of µg m -3 ) in daytime is higher than that in nighttime, whereas the relative increasing trend (in a unit of %) in daytime is lower than that in nighttime (Figures 4e-4h vs. which is probably related to the hot extremes in 2017 (Herring et al, 2019).…”
Section: Seasonal and Interannual Variations Of Surface Ozone In Eastmentioning
confidence: 64%
See 1 more Smart Citation
“…Silver et al (2018) found the annual mean MDA8 ozone has increased significantly (p<0.05) at around 50% of the over 1000 stations across China from 2015 to 2017, with a median rate of 4.6 µg m -3 year -1 . The increasing trend over eastern China was also captured by the OMI satellite records of tropospheric ozone, reported by Shen et al (2019). The absolute increasing trend (in a unit of µg m -3 ) in daytime is higher than that in nighttime, whereas the relative increasing trend (in a unit of %) in daytime is lower than that in nighttime (Figures 4e-4h vs. which is probably related to the hot extremes in 2017 (Herring et al, 2019).…”
Section: Seasonal and Interannual Variations Of Surface Ozone In Eastmentioning
confidence: 64%
“…A rapid increasing trend in summertime surface ozone over China after 2012 was observed in recent studies (Lu et al, 2018;Silver et al, 2018;Shen et al, 2019;. We examine the regional mean trend over eastern China in daily, daytime (7:00-18:00), and nighttime (19:00-6:00) means ( Figure 4).…”
Section: Seasonal and Interannual Variations Of Surface Ozone In Eastmentioning
confidence: 94%
“…3.4. The warmer and drier weather conditions in May-August 2017 are expected to accelerate ozone production rates and also favor the thermal decomposition of peroxyacetyl nitrate (PAN, a NO x reservoir species whose decomposition is strongly temperature dependent), providing additional NO x to produce ozone (Steiner et al, 2010;Doherty et al, 2013). This is evident from the lower background PAN concentrations (model results in noCH only reflect changes in meteorology) over eastern China simulated in 2017 ( Fig.…”
Section: Factors Contributing To the Ozone Increase From 2016 To 2017mentioning
confidence: 99%
“…The increase in ozone over China may result from both meteorology and anthropogenic emissions. During 2013-2017, the anthropogenic emissions of NO x in China declined (Zheng et al, 2018), but the anthropogenic emissions of VOCs changed little (Zheng et al, 2018;Shen et al, 2019b). Li et al (2019) suggested that the ∼ 40 % decrease in fine particulate matter (PM 2.5 ) is the primary reason for the rising surface ozone in summer during 2013-2017, as the aerosol sink of hydroperoxy radicals was weakened and thus ozone production was enhanced.…”
Section: Classification Of the Synoptic Weather Patternsmentioning
confidence: 99%